PENGARUH KUALITAS PELAYANAN, NILAI PRODUK DAN FASILITAS TERHADAP KEPUASAN NASABAH (STUDI PADA NASABAH TABUNGAN MUDHARABAH AL BARAKAH DI BANK KALSEL KANTOR CABANG SYARIAH BANJARMASIN) - Muhammad Fajri Muhtadi; Emy Rahmawati; Setio Utomo (Universitas Lambung Mangkurat, 2020)
Customer-oriented marketing strategies, make companies must understand and fulfill both the behavior and needs of customers to achieve customer satisfaction. Consumer satisfaction is greatly considered by the company because it will have an impact on sales performance. South Kalimantan Bank seeks to improve its image as a banking financial institution, one of the efforts taken is to maximize value holders by providing excellent service and describing it in the main behaviors of Bank Kalsel employees in serving customers' needs, namely empathizing and serving wholeheartedly, being polite and polite, and is responsive in meeting the needs of stake holders.This study aims to examine the influence Service Quality (X1), Product Value (X2) and Facilities (X3) of the Customer Satisfaction (Y) on Bank Branch Office Banjarmasin in South Kalimantan well se a way partially or simultaneously. 99 samples were taken customer by using the Slovin formula. Data collection uses a questionnaire while the data analyst is using Multiple Linear Regression Analysis through the SPSS version 23 program.The test results prove that Service Quality has a significant effect on Customer Satisfaction in partial with a large effect of 72.7 % including a very strong category , Product Value has a significant effect on Customer Satisfaction partially with a large effect of 49.2 % including the fairly strong category , the Facility has a significant effect on Customer Satisfaction in part with a significant effect of 36.9 % including the category is quite strong while simultaneously Service Quality Leadership , Product Value, and Facilities have a significant effect on Customer Satisfaction with the influence of 65.8 % including thevery strong category while the remaining 34.2 % is influenced by other variables.Keywords: Service Quality, Value of Products, Facilities and Customer Satisfaction